Direct Solar‐to‐Electrochemical Energy Storage in a Functionalized Covalent Organic Framework. (3rd September 2018) - Lv, Jiangquan; Tan, Yan‐Xi; Xie, Jiafang; Yang, Rui; Yu, Muxin; Sun, Shanshan; Li, Ming‐De; Yuan, Daqiang; Wang, Yaobing
Abstract: A covalent organic framework integrating naphthalenediimide and triphenylamine units (NT‐COF) is presented. Two‐dimensional porous nanosheets are packed with a high specific surface area of 1276 m 2 g −1 . Photo/electrochemical measurements reveal the ultrahigh efficient intramolecular charge transfer from the TPA to the NDI and the highly reversible electrochemical reaction in NT‐COF. There is a synergetic effect in NT‐COF between the reversible electrochemical reaction and intramolecular charge transfer with enhanced solar energy efficiency and an accelerated electrochemical reaction. This synergetic mechanism provides the key basis for direct solar‐to‐electrochemical energy conversion/storage. With the NT‐COF as the cathode materials, a solar Li‐ion battery is realized with decreased charge voltage (by 0.5 V), increased discharge voltage (by 0.5 V), and extra 38.7 % battery efficiency.